Penentuan Kelayakan Fungsi untuk Pemodelan Pemanasan Minyak Mentah menggunakan Energi Gelombang Mikro: Yustiana Yustiana, Melania Suweni Muntini, Yono Hadi Pramono - Yustiana, Yustiana; Melania Suweni Muntini, Melania Suweni Muntini; Yono Hadi Pramono, Yono Hadi Pramono (Jurnal Fisika dan Aplikasinya, 2025)
Due to the high demand of energy supply, a development in petroleum processing technology is required. One of the important processes in the petroleum processing is the heating process, which conventionally can reduce the oil production. This study aims to create a real-time modeling of crude oil heating process using microwave energy in an oil well pipe. In addition, this heating technique aims to reduce the viscosity and reduce the amount of residual particles, as well as to minimize the production cost. The secondary data were obtained, and subsequently being modeled and analyzed using NSD parameter (Normalized Square Deviation) to determine the feasibility of the function. Modeling results indicate that the temperature of the oil from the surface to the depth of the well pipe decreases exponentially. While the oil temperature from the center to the edge of the cylindrical pipe decreases sinusoidally. The microwave source has a power of 500 W and a maximum temperature produced of 3850 C in 10 s.